Risiko gangguan muskuloskeletal pada pekerja pengemasan keripik tempe - Isti Purwaningsih; Siti Asmaul Mustaniroh; Andan Linggar Rucitra; Keane Listyadji (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Packing tempeh chips in the XYZ business unit is carried out in a sitting position on the floor, body slightly bent, head down, and legs bent. These conditions need to be corrected so as not to cause injuries and musculoskeletal disorders (MSDs). This study aims to determine the risk level of MSDs in tempeh chip packaging workers using the QEC (Quick Exposure Check) and REBA (Rapid Entire Body Assessment) methods. The study was conducted at the XYZ tempeh chips business unit in Malang City. The research subjects were workers in the packaging section. Data collection was carried out in two stages: a survey of musculoskeletal symptoms using the NBM (Nordic Body Map) questionnaire and a questionnaire to assess the level of risk based on the QEC method. The second stage is the evaluation of work posture with the REBA method. The results showed that the complaints of pain felt by workers were in the upper neck, left shoulder, back, and left and right calves. Complaints of severe pain in the right shoulder, waist, and left and right legs. The MSDs risk level based on the QEC method shows that all tasks are at the exposure level of 52.3% – 62.5%, and immediate corrective action is taken. Based on the REBA method, a 7-12 was obtained, indicating that the risk of MSDs ranged from moderate to high. Corrective action needs to be taken immediately for high risk. Corrective action is needed now for very high risk. To reduce the risk of MSDs are improving work posture by improving the layout of packaging facilities, adding work facilities, and setting working time standards to set appropriate minimum packaging targets.